2008
DOI: 10.1186/1471-2202-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Neurospheres from rat adipose-derived stem cells could be induced into functional Schwann cell-like cells in vitro

Abstract: Background: Schwann cells (SC) which are myelin-forming cells in peripheral nervous system are very useful for the treatment of diseases of peripheral nervous system and central nervous system. However, it is difficult to obtain sufficient large number of SC for clinical use, so alternative cell systems are desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 36 publications
4
85
0
1
Order By: Relevance
“…In support of this, human ASCs can form nestin-positive neurospheres that, upon dissociation, express characteristic SC markers like S100, GFAP, and the p75 NGF receptor [123]. Similar markers have also been seen in rat ASCs induced with mixture of glial growth factors [130,131]. Moreover, SC-induced ASCs also appear to possess functional capacity, demonstrating the ability to stimulate neurite outgrowth of dorsal root ganglia neurons (DRGNs) under coculture [123,132], NG108-12 motor neurons [130], and SH-SY5Y neuroblastoma cells [131].…”
Section: Increased Potential Of Ascs: In Vitro Ectodermal Capacitymentioning
confidence: 66%
“…In support of this, human ASCs can form nestin-positive neurospheres that, upon dissociation, express characteristic SC markers like S100, GFAP, and the p75 NGF receptor [123]. Similar markers have also been seen in rat ASCs induced with mixture of glial growth factors [130,131]. Moreover, SC-induced ASCs also appear to possess functional capacity, demonstrating the ability to stimulate neurite outgrowth of dorsal root ganglia neurons (DRGNs) under coculture [123,132], NG108-12 motor neurons [130], and SH-SY5Y neuroblastoma cells [131].…”
Section: Increased Potential Of Ascs: In Vitro Ectodermal Capacitymentioning
confidence: 66%
“…Both populations presented identical cell size, doubling times and karyotype stability, differing only in morphology with rounder cells in the sub-odontoblastic compartment versus spindle-shaped cells with long processes in the perivascular one [239]. Pre-clinical experiments have demonstrated that stem cells show promising results in differentiation into neuronal-like cells [226,228,232,233,240] and their secretion of growth factors [229,241,242]. Shi and colleagues [243] stated the potential of glia-derived neurotrophic factor expressing neural stem cells in the regeneration of facial nerve gap in rats.…”
Section: Cellular Systemsmentioning
confidence: 99%
“…Other sources of stem cells have been used in peripheral nerve injuries, such as adipose-derived stem cells [203,206,212,[226][227][228][229][230][231] and dental pulp stem cells (DPSCs) [232][233][234][235][236]. Dental pulp stem cells have also demonstrated differentiation capacity towards multiple other mesodermal and endodermal lineages, under appropriate conditions: adipogenic, osteo/dentinogenic, chondrogenic, neurogenic, endothelial, myofibroblastic [237] and hepatocytes [238].…”
Section: Cellular Systemsmentioning
confidence: 99%
“…Unlike BMSCs, donor age and site of harvest does not seem to significantly influence the therapeutic effect of ADSCs [50] . Multiple neuronal and SC markers have been expressed from differentiated ADSCs [7,30,[95][96][97] . The expression of myelin protein zero, peripheral myelin protein-22 and myelin basic protein also suggest the retention of myelinating capability [98] .…”
Section: Bone Marrow Derived Stem Cellsmentioning
confidence: 99%